Deciphering the effects of agglomeration economies on firms' productive efficiency - Dimitris Skuras; Kostas Tsekouras; Efthalia Dimara (European Regional Science Association (ERSA), 2011)
The present work assess the effects of MAR and Jacob's type agglomeration economies on a sample of firms in the machineries and textiles industries in Greece for the periods 1989-91 and 1999-01. The analysis employs a stochastic production frontier function and allows agglomeration economies to enter as inputs and/or as factors reducing inefficiency. Results re-confirm that the effects of agglomeration economies are industry specific. In our study, the machineries industry benefits from MAR type agglomeration economies and the textiles industry benefits from Jacob's type agglomeration economies. Agglomeration economies may exercise a twin effect on firms' productive efficiency. First, as in the case of the machineries industry in our study, MAR agglomeration economies may act as a new input and affect the kernel of the production frontier. Second, agglomeration economies may act as a factor reducing technical inefficiency with non-neutral effects with labour and capital as in the case of both the machineries and the textiles industries in our study. Finally, it is indicated that agglomeration economies establish a type of "path dependence" for firms. Firms that make significant use of agglomeration economies survive to the next period at higher percentages in comparison to other firms in the same industry. At the same time, entrants are favoured by MAR type agglomeration economies while incumbents are favoured by Jacob's type agglomeration economies.
Keywords: 330